Incidence and predictors of arrhythmias in patients with systemic sclerosis and no overt cardiac disease. (25th November 2020) - Stronati, G; Manfredi, L; Dichiara, C; Dello Russo, A; Gabrielli, A; Guerra, F
Abstract: Background: Cardiac involvement in SSc is frequent, mostly subclinical and represents a negative prognostic factor. Speckle tracking derived measurement global longitudinal strain (GLS) has been able to identify primary heart involvement in patients with SSc and no overt cardiac disease. SSc-related cardiomyopathy, defined as a condition affecting the heart primarily and globally, has been proven to progress over time and seems to be correlated to cardiac arrhythmias. Nonetheless, cardiac arrhythmias represent 6% of the overall causes of death in SSc patients. Purpose: The aim of our study was to assess the incidence of cardiac arrhythmias in SSc patients with no overt cardiac disease and to identify potential predictors. Methods: Prospective longitudinal study enrolling all consecutive patients with a diagnosis of SSc and no overt cardiac disease or pulmonary hypertension. Echocardiographic parameters and GLS were obtained at baseline and at each follow up. Presence of atrial fibrillation (AF), atrial tachycardia (AT), ventricular ectopic beats >1000/24 h (VEB), supraventricular ectopic beats (SVEB), bundle branch block (BBB) and atrioventricular block (AVB) was assessed through clinical history, ECG and 24-Holter monitoring over time. Results: Among 67 consecutive patients with SSc, 11 (16.7%) had at least one episode of AF or AT. Moreover, respectively 12 (17.9%) and 16 (23.9%) had a significant amount of SVEB and VEB at Holter monitoring. Conduction defects were common, with 4 (4.6%) of all patients with grade I AVB, 1 (1.5%) with grade II AVB and 1 (1.5%) with complete heart block. Complete right BBB was seen in 6 (6.9%) of patients. Four patients (4.6%) experienced a sudden cardiac death during follow-up (median 20 months, 1st-3rd quartile 12–24 months). Years from SSc diagnosis (RR 1.10; 95% CI 1.02–1.23; p=0.047) and indexed right atrial volume (iRAV; RR 1.22; 95% CI 1.07–1.39; p=0.004), but not indexed left atrial volume were independently correlated with the diagnosis of AF/AT. The same two variables were independently correlated with any degree of AV block (years from SSc diagnosis: RR 1.11; 95% CI 1.01–1.23; p=0.004; iRAV: RR 1.14; 95% CI 1.02–1.27; p=0.019). Due to the low sample size, we were unable to detect any clinical predictors of sudden cardiac death in our population, however those who died experienced a larger worsening in left ventricle GLS values (4.0±1.6 vs. 0.9±0.4, p=0.056). Conclusions: Supraventricular arrhythmias and conduction defects are common in patients with SSc. Time from diagnosis and right atrial volumes are able to predict the incidence of such conditions, supporting the hypothesis that a long-lasting disease and the anatomical remodelling of the right atrium could contribute to the developing of tachy- and bradyarrhythmias in this population. Funding Acknowledgement: Type of funding source: None